Edukasi Penerapan Internet Sehat dan Aman Bagi Siswa Siswi SMK SATU NUSA 3 Bandar Lampung - Sevi Andriasari; Muhammad Ferdiansyah (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
The internet today is a part of mass media, where the fact shows that the mass media has a very large role in the lives of people. The internet has even become an inseparable part of people’s lives and lifestyles. Through the internet people can communicate with someone or even with several communities all at once. The current phenomenon shows that the internet is somehow misused, for instance, accessing pornographic sites, which is a problem that has a large impact on the future survival of the younger generation, as well as the tendency of the younger generation towards online and offline games. The crime happens online commonly called cybercrime has reached to the action of hacking important sites in the country. To avoid crimes in cyberspace, students of SMK ONE NUSA 3 Bandar Lampung are given education about how to surf the internet in a healthy and safe manner which always emphasizes the basic principle that must be known in using the internet. The application of the internet in a healthy and safe way needs to be instilled from an early age through learning internet ethics or commonly called netiquette, so that it can avoid bad habits in the real world that will carry over in cyberspace and recreate negative influences in the real world.